Proline-catalyzed sequential syn-mannich and [4+1]-annulation cascade reactions to form densely functionalized pyrrolidines - Aher, Ravindra D.; Kumar, B. Senthil; Sudalai, Arumugam (Journal of Organic Chemistry, 2015)
A highly efficient one-pot [4 + 1]-annulation process for the asymmetric synthesis of densely functionalized pyrrolidine derivatives is described. The in situ generated syn-Mannich adduct obtained via proline catalysis acts as a four-atom component, and Coreys sulfur ylide or ethyl bromoacetate acts as a one-atom carbon source to construct pyrrolidine units in a highly enantio- and diastereoselective manner.

Proline catalyzed enantioselective synthesis of (2S,3S)-3-hydroxypipecolic acid and formal synthesis of (+)-swainsonine - Aher, Ravindra D.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
A short enantioselective synthesis of (2S,3S)-3-hydroxypipecolic acid (overall yield: 18.8%; 96% ee) and formal synthesis of (+)-swainsonine (overall yield: 13.6%; 96% ee) have been described starting from commercially available acrolein. The synthetic strategy involves a high enantioselective L-proline catalyzed sequential c-amination and diastereoselective (dr > 99:1) Barbier allylation of aldehyde in one-pot as the key reaction. (C) 2016 Elsevier Ltd. All rights reserved.